Digital Fourier Analysis: Advanced Techniques - Kido, Ken'iti (Springer, 2015)
This textbook is a thorough, accessible introduction to advanced digital Fourier analysis for advanced students. Assuming knowledge of the Fast Fourier Transform, this book covers advanced topics including the Hilbert transform, cepstrum analysis and the two-dimensional Fourier transform.